Investigation of chronic diarrhoea. Issue 10 (October 2016) - Auth, Marcus K.H.; Vora, Rakesh; Kokai, George
Abstract: Chronic diarrhoea occurs, by definition, when there is an excessive intestinal loss of water and electrolytes with increased stool frequency, reduced consistency and larger volume over more than 14 days. While in developing countries often resulting from persisting infectious gastroenteritis in high incidence, in industrialized countries chronic diarrhoea is mainly related to anatomical, functional, and immunological causes. As the spectrum of aetiology is variable, flow charts for different age groups are useful in determining key features of disease severity and diagnostic criteria. The knowledge of common and rare aetiologies enables a structured approach to investigation, and facilitates critical interpretation of results in awareness of diagnostic pitfalls. Comprehensive history, physical examination, inspection and collection of stool samples of sufficient volume are pivotal to devise appropriate referral modes for diagnostic and therapeutic management, as particularly newborn and infants are susceptible to severe dehydration and metabolic disturbances.